Practicing of Corporate Social Responsibility for Community Empowerment: A Case of a Mining Company in Indonesia - Alamsyah Agus (Randwick International of Social Science Journal, 2020)
In recent years, Corporate Social Responsibility (CSR) has attained increased significance in both business and in the associated academic literature. The very term, CSR, clearly indicates the focus is on social responsibility as a company’s obligation to be accountable to all its stakeholders in all its operations and activities. Nowadays the concept of empowerment has become the development paradigm. The Indonesian government is expected to coordinate and be responsible for a wide range of community development activities that allow the entire community to participate actively, while the company contributes to the community empowerment process as the implementation of social responsibility undertaken through its Corporate Social Responsibility (CSR). This study assessed the CSR activities undertaken by a mining company (PT Vale Indonesia). Over the past 50 years, PT Vale Indonesia (PTVI) has been operating under the Contract of Work (CoW) agreement with the Indonesia government to open-pit nickel mines and processing plant facilities near Sorowako, Indonesia. This study provided empirical evidence on PTVI's presence benefits the surrounding communities by implementing PTVI’s CSR program called Integrated Community Development Program (ICDP). The research purpose is to explore the concept of CSR practice that is viewed and applied by PTVI to create a win-win situation that contributes to community empowerment. The findings of this case study contribute significantly to give more profound knowledge of the role of ICDP to community empowerment and to extant an understanding of the company dealing with the challenges of CSR activities for community empowerment.